COMPORTAMENTO INGESTIVO DE BOVINOS DE CORTE EM PASTEJO RECEBENDO ADITIVO À BASE DE FITOTERÁPICO - LARA, Renato Oliveira Dorna; PERDIGÃO, Alexandre; MORAES, Luana Prado; CERUTTI, Thays Conrado; FERNANDES, Henrique Jorge; SILVA JUNIOR, Jarbas Miguel da (ANAIS DO ENIC, 2026)
.